DEVELOPMENT OF A RADIOPHARMACEUTICAL (PART I): PREPARATION OF A DIAMINEDITHIOL TYPE LIGAND FOR USE IN NUCLEAR MEDICINE - Robles Ñ., Ana (2001)
In renal function study the Diaminodithiol (DADT) complexes with Te 99m have an advantage due to the great absortion in the kidneys and the fast removal by urine. Among these compiexes, the N,N·-bis-L-( 1-carboxi-2-mercaptoethyl) ethylendiamine (EC) which form an stable complex with oxotechnetium (V) ot tetragonal structure exhibit better results. In this work an study about its preparation is presented.